2020
DOI: 10.3390/cells9102148
|View full text |Cite
|
Sign up to set email alerts
|

The Absence of NLRP3-inflammasome Modulates Hepatic Fibrosis Progression, Lipid Metabolism, and Inflammation in KO NLRP3 Mice during Aging

Abstract: Aging is associated with metabolic changes and low-grade inflammation in several organs, which may be due to NLRP3 inflammasome activation. Methods: Here, we asked whether age-related liver changes such as lipid metabolism and fibrosis are reduced in aged mice lacking the NLRP3 inflammasome. We report reduced protein levels of lipid markers (MTP, FASN, DGAT1), SOD activity, oxidative stress marker PTPRG, and the fibrotic markers TPM2β, COL1-α1 associated with increased GATA4, in NLRP3 deficient mice. Fibrotic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 22 publications
(28 reference statements)
1
20
0
Order By: Relevance
“…We also investigated whether NLRP3 inflammasome activation could be involved in TMAO-induced fibroblast proliferation. A variety of studies support the association of the NLRP3 inflammasome with fibrosis, TMAO, Akt and mTOR [22,23,[64][65][66][67]. Using NLRP3 and caspase-1 knockout cell lines, we found that the proliferative effect of TMAO on human renal fibroblasts is NLRP3 and caspase-1 dependent.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…We also investigated whether NLRP3 inflammasome activation could be involved in TMAO-induced fibroblast proliferation. A variety of studies support the association of the NLRP3 inflammasome with fibrosis, TMAO, Akt and mTOR [22,23,[64][65][66][67]. Using NLRP3 and caspase-1 knockout cell lines, we found that the proliferative effect of TMAO on human renal fibroblasts is NLRP3 and caspase-1 dependent.…”
Section: Discussionmentioning
confidence: 57%
“…According to Artlett et al, chronically activated NLRP3 inflammasome leads to constant ECM synthesis and induction of fibrosis by maintaining fibroblasts in their activated state or by keeping a high level of TGF-β1 via IL-1β production [22,23]. Moreover, there is evidence that NLRP3 inflammasome has a role in lung [23] and liver [64] fibrosis. Regarding the effect of TMAO on NLRP3 inflammasome, it has been shown that the TMAO increases the activation of the NLRP3 inflammasome in carotid arteries of mice [65].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive ROS production is an important process for the activation of inflammasome complexes (70)(71)(72). The NLRP3 inflammasome has been reported to be extensively expressed in the liver (20,73). Previous studies have reported that the NLRP3 inflammasome was activated in the progression of alcoholic liver disease (ALD), and liver inflammation and steatosis were significantly improved in ALD mice with knocked out NLRP3 or caspase-1 expression (74,75).…”
Section: Discussionmentioning
confidence: 99%
“…These results also discovered that the arrangement of hepatocytes was abnormal and disordered and most of the cells appeared to have vacuole-like degeneration in the SAMP8 group, while Rg1 treatment showed a significant improvement in liver histopathology. In addition, the results discovered that NOX4/NLRP3 inflammasome signaling, which is closely associated with age-related liver injury and liver fibrosis ( 20 ), was significantly inhibited by Rg1 (5 and 10 mg/kg) treatment, especially in the Rg1 (10 mg/kg) group. These results suggested that Rg1 treatment may be effective in preventing aged-related injury and fibrosis in a dose-dependent manner, possibly by inhibiting NOX4 and the NLRP3 inflammasome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation